Grameen Bank and Muhammad Yunus - Yunus, Muhammad, 1940-; Ahsan, Mohammad Badrul (Dhaka : Mowla Brothers, 1996)
Collection of interviews given by Muhammad Yunus, founder and managing director of Grameen Bank, to the national and foreign press in Bangladesh.
Keywords: Grameen Bank; Yunus, Muhammad, -- 1940-